THE EFFECT OF TOFU DUMP SUBSTITUTION ON THE CHEMICAL CHARACTERISTICS AND SENSORY QUALITY OF CHICKEN SAUSAGE - Vincentius Soeyoto; Yuyun Yuniati; Bambang Sigit Sucahyo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Chicken sausage is a widely consumed processed meat product, but its relatively high production costs and low fiber content encourage the need for innovative formulations based on alternative ingredients. Tofu dregs, a byproduct of the tofu industry, contain vegetable protein and dietary fiber that have the potential to be used as a substitute ingredient in making chicken sausages. This study aims to analyze the effect of tofu dregs substitution on the chemical and organoleptic qualities of chicken sausages. The research method used was a laboratory experiment with a one-factor completely randomized design, namely tofu dregs substitution levels of 10%, 30%, 50%, and 60%. Parameters observed included protein, fat, and carbohydrate levels, as well as organoleptic tests for color, aroma, texture, and taste using a hedonic scale. Chemical quality data were analyzed using ANOVA, while organoleptic data were analyzed nonparametrically. The results showed that tofu dregs substitution affected the chemical quality and organoleptic acceptance levels of chicken sausages. Substitution at certain levels was able to increase fiber content without significantly reducing consumer acceptance. This study shows that tofu dregs have the potential to be used as a substitute ingredient in making chicken sausages to produce a more nutritious and sustainable product.